Study of the Engineering Design of a Single-Cylinder High-Pressure Steam Engine with a Corliss Valve Gear - José Ignacio Rojas-Sola; Santiago Sánchez-García (Applied Sciences)
This paper presents an engineering design-based investigation of a historical invention: a single-cylinder horizontal high-pressure steam engine with a Corliss valve gear designed by Arnold Throp. The research, grounded in engineering drawing, has enabled an understanding of the operation of this invention based on a 3D CAD model derived solely from original plans published in the Model Engineer magazine in 1982 and reproduced by Julius de Waal in 2018. Contributing to the field of industrial archeology, our novel research utilizes CAD, engineering drawing, and mechanical engineering principles to revitalize historical inventions. Our methodology allows for a detailed analysis of the design and function of these significant technological advancements, ensuring their legacy is preserved. However, challenges were encountered during the geometric modeling process due to missing dimensions for certain components and errors in others. To address these issues, dimensional, geometric, and kinematic constraints (degrees of freedom) had to be applied to ensure that the 3D CAD model was coherent and functional, and an interference analysis also had to be conducted. Ultimately, symmetry was discovered in the governor’s structure and the arrangement of the four valves within the cylinder block, particularly in the mechanism that operates the inlet valves. This symmetry is essential to ensure that forces and movements are distributed evenly during the steam exchange within the cylinder, allowing for more balanced work, reduced vibrations, and the optimization of the overall efficiency of the invention.